Determination of Transportation Fleet Size using The Combination of Adjusted SPT Rule and Linear Programming Method - Saroyo, Pujo; Wibowo, M.P.A (KnE Life Sciences, 2016)
In a very competitive industry, XYZ Ltd. needs to have an effective, efficient and reliable logistics fleet management. The fleets should be able to help the company serve the market demands and guarantee the distribution of its products. This research analyzed and determined the by-truck transportation fleet size of XYZ Ltd using the combination of adjusted SPT Rule and linear programming method. The results showed that the product delivery’s scheduling was arranged by operating a fleet of 13 tronton trucks and 25 trailer trucks, with the scheduling of delivery resulting in maximum makespan of 6.98 days and an average flow-time per shipment of 3.83 days. Keywords: Fleet Management, Logistics Transportation, Adjusted SPT